PENERAPAN PASAL 28 AYAT (2) UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DALAM MENANGGULANGI DELIK UJARAN KEBENCIAN DI INTERNET - Windisen Windisen; Ade Adhari (Universitas Muhammadiyah Ponorogo, 2021)
Hate speech is an act that is prohibited by law, with the development of technology, information and communication, hate speech is also found on the internet. Regulations regarding hate speech offenses on the internet in Indonesia are formulated in Article 28 paragraph (2) of Law Number 11 of 2008 concerning Electronic Information and Transactions as amended by Law Number 19 of 2016 concerning Electronic Information and Transactions (UU ITE). However, in its application, Article 28 paragraph (2) of the ITE Law is considered problematic and does not provide legal certainty. Therefore, the problem formulated, namely